2010
DOI: 10.1186/1471-2458-10-101
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh Addiction Cohort: recruitment and follow-up of a primary care based sample of injection drug users and non drug-injecting controls

Abstract: BackgroundInjection drug use is an important public health problem. Epidemiological understanding of this problem is incomplete as longitudinal studies in the general population are difficult to undertake. In particular little is known about early life risk factors for later drug injection or about the life course of injection once established including the influence of medical and social interventions.MethodsIndividuals thought to be drug injectors were identified through a single primary medical care facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…These exposures appeared under‐recorded in clinical records, making an analysis including dead cases, using exposure information from records, potentially misleading. We investigated other possible administrative sources of early life exposure information, such as social services records, but accessing these proved unfeasible . Bias may have been introduced through control selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These exposures appeared under‐recorded in clinical records, making an analysis including dead cases, using exposure information from records, potentially misleading. We investigated other possible administrative sources of early life exposure information, such as social services records, but accessing these proved unfeasible . Bias may have been introduced through control selection.…”
Section: Discussionmentioning
confidence: 99%
“…Bias may have been introduced through control selection. An historical sampling frame could not be constructed in order to select a control from the same time as case recruitment . Controls were selected conditional on their attendance at a primary health‐care facility; given the typical population frequency of attendance in primary care, it is likely that most potential controls attended during the recruitment period; however, individuals with poorer health probably attended at a higher frequency and may be over‐represented among our controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macleod et al [11] reported that the first drug injection of their cohort was at the age of 19) and as, furthermore, a large subgroup of addicted patients show symptoms of personality disorders [12], we hypothesized that most patients would (a) fulfill the diagnostic criteria for at least one DSM-IV personality disorder and (b) be located at a borderline level of personality organization (PO) according to Kernberg's model [13]. Also, we hypothesized (c) to find a significant relationship between severity of addiction and severity of personality pathology.…”
Section: Introductionmentioning
confidence: 99%